The Effect of Outpatient Medical Consultation Experience on Overall Satisfaction and Intention to Recommend - Lydia Priscillia Pomantouw; Ferdi Antonio (Indonesian Journal of Global Health Research, 2026)
Patient-centred care has increased the importance of understanding patient experience during outpatient medical consultations, particularly in primary care clinics where doctor–patient interaction plays a central role in service quality. While patient satisfaction is known to influence recommendation behaviour, most studies rely on general service quality dimensions rather than consultation-specific experiences, especially in the Indonesian clinical context. This study aims to examine the effect of outpatient medical consultation experience on overall satisfaction with medical consultation and to analyse its impact on patients’ intention to recommend the clinic. A quantitative cross-sectional survey was conducted among outpatients at XYZ Clinic in Manado, Indonesia. Data were collected from 168 respondents using a structured questionnaire developed by synthesising domains from the Medical Interview Satisfaction Scale (MISS) and Consultation Satisfaction Scale (CSQ), namely communication comfort, rapport, length of consultation time, distress relief, and professional care. Construct validity and reliability were assessed using factor loadings, average variance extracted (AVE), composite reliability, and Cronbach’s alpha prior to structural model testing. Data were analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The findings demonstrate that all five consultation experience dimensions have a significant and positive influence on overall satisfaction with medical consultation. Communication comfort emerged as the strongest predictor.